Current Evidence on Vitamin D Deficiency and Metabolic Syndrome in Obese Children: What Does the Evidence from Saudi Arabia Tell Us? - Asma M. Alaklabi; Naser A. Alsharairi (MDPI AG, 2018)
Obesity and vitamin D deficiency represent major health problems among Saudi children, and have been linked to chronic diseases. Obese children are at risk of developing vitamin D deficiency, which appears to have negative influences on energy homeostasis, impeded bone mineralisation, insulin resistance and inflammation. Evidence supporting the association between vitamin D deficiency of obese children and metabolic syndrome has not specifically been studied in early childhood. The mechanisms through which vitamin D deficiency is associated with metabolic syndrome in obese children needs further elucidation. This commentary aims to (i) summarise current knowledge of the association between vitamin D deficiency and metabolic syndrome in obese children; and (ii) discuss current evidence for the association among Saudi Arabian children.